PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE (ENE) TERHADAP KEMAMPUAN MENULIS DESKRIPSI PADA SISWA KELAS IV SEKOLAH DASAR - Vina Munawaroh; Idham Kholid; Nurul Hidayah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This study aims to determine the effect of Example Non-Example (ENE) learning model in improving students' writing description skills. Example Non-Example (ENE) learning model is a type of learning that utilizes images in conveying learning material. Students are required to analyze the picture shown by the educator then pour it into the written description. This research method is a kind of quantitative research types quasy Experiment Design. The population in this study were all grade IV students of SD Muhammadiyah 1 Bandar Lampung. The sample in this study was class IV C as an experimental class, and class IV A as a control class. The sampling technique is to use the Simple Random Sampling technique. Data analysis techniques using the normality test, homogeneity test, and hypothesis testing (t-test). Based on the results of this study there is the influence of the Example Non Example (ENE) learning model and the conventional learning model on the writing skills of the students' description. That is, there is the influence and the difference between the experimental class and control class.